2021
DOI: 10.1155/2021/8968464
|View full text |Cite
|
Sign up to set email alerts
|

Si-Miao-Yong-An Decoction Maintains the Cardiac Function and Protects Cardiomyocytes from Myocardial Ischemia and Reperfusion Injury

Abstract: Objective. The aim of this study was to determine whether Si-Miao-Yong-An decoction (SMYAD) could protect cardiomyocytes from ischemia/reperfusion (I/R) injury and its underlying mechanisms. Methods. C57BL/6 mice were used to establish a model of myocardial infarction by I/R injury and treated by SMYAD for 4 weeks. Then, the cardiac functions of mice were evaluated by cardiac magnetic resonance (CMR). Histopathological analysis for the heart remodeling was detected by H&E and Masson staining. The protein e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Thus, HJ11 decoction might intensify the metabolic rate of rats with myocardial I/R injury, which further resulted in a higher ROS level than that in rats of the Sham group. Mitochondrial damage is the main morphological characteristic feature of ferroptosis, such as shrinkage of the mitochondria and broken mitochondrial cristae (Cui et al, 2021). The mitochondrion is a major organelle involved in ATP production to provide the necessary cellular energy.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, HJ11 decoction might intensify the metabolic rate of rats with myocardial I/R injury, which further resulted in a higher ROS level than that in rats of the Sham group. Mitochondrial damage is the main morphological characteristic feature of ferroptosis, such as shrinkage of the mitochondria and broken mitochondrial cristae (Cui et al, 2021). The mitochondrion is a major organelle involved in ATP production to provide the necessary cellular energy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a study showed that Simiaoyong An Decoction (SMYAD) had a protective effect on myocardial ischemia/reperfusion injury by activating autophagy and inhibiting pyroptosis, and improving the cardiac function of cardiomyocytes. The mechanism is that SMYAD increases the protein expression rate of LC3B-II/LC3B-I in H/R cardiomyocytes, reduces the protein expression rate of p-mTOR/mTOR, and downregulates the expression of Caspase-1, NLRP3, and IL-1β ( 105 ).…”
Section: Relationship Between Autophagy and Pyroptosismentioning
confidence: 99%
“…In vitro experiments showed that SMYAD protected H9C2 cardiomyoblast cells from hyperoxia/reoxygenation (H/R). The in-depth experiment revealed that SMYAD upregulated the expression rate of LC3B-II/LC3B-I, reduced the expression rate of p-mTOR/mTOR, and downregulated the expression of NLRP3, caspase 1, and IL-1β in H/R cardiomyocytes, indicating that SMYAD activated autophagy and inhibited pyroptosis [ 83 ]. Our previous studies have shown that autophagy can be activated through the AMPK/mTOR pathway [ 84 ].…”
Section: The Role Of Pyroptosis and Autophagy In Myocardial Ischemia ...mentioning
confidence: 99%